Qualitative assessment of barriers perceived by women using perception scale of barriers in contraceptive use as measurement tool - D., Sreesubhageetha; Krishnan, Niveditha; P., Padmavathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study was conducted to determine the barriers and obstacles perceived by women with regard to contraceptive use by using perception scale barriers in contraceptive use (PSBCU) as the measurement tool in women utilizing the family planning services. Methods: It was a cross-sectional study conducted amongst 300 reproductive age group of women. Perception scale of barriers to contraceptive use was designed as 5-point Likert scale and the scale contains three dimensions. The domains were emotional dimension (10 items), social dimension (8 items) and cognitive dimension (9 items). The scale was administered using face to face interview. Each perceived obstacle was assessed by women using 5-point Likert scale ranging from strongly agree (score 5) to strongly disagree (score 1). The lowest score obtainable from the scale was 27 whereas the highest score was 135. Highest score indicates maximum barriers. Results: By administering PSBCU scale, a maximum score was obtained for intra uterine contraceptive devices and a minimum score obtained for DMPA. Therefore, this study showed that intra uterine contraception devices have the highest barriers and long acting injectable-DMPA has lowest barriers. Conclusions: A scale like PSBCU will be useful to know about the experience of current contraception and obstacles perceived and thereby addressing the issues to improve the uptake of contraception services and as well as to reduce the discontinuation rates.